FRI0361 Pregnancy outcomes and therapy in systemic lupus erythematosus: results from our 30 years' experience pregnancy clinic. (12th June 2018) - Crisafulli, F.; Lazzaroni, M.G.; Andreoli, L.; Gerardi, M.C.; Antolini, L.; Parma, G.; Benigno, C.; Lojacono, A.; Zatti, S.; Cappa, V.; Calza, S.; Franceschini, F.; et al.
Abstract : Background: The outcome of Systemic Lupus Erythematosus(SLE) pregnancies has dramatically improved thanks to pregnancy planning, multidisciplinary management and close monitoring during pregnancy. In our experience, programmed pregnancies in SLE patients had similar rates of pregnancy losses as compared to general obstetric population, but there are still open issues on some pregnancy complications that more frequently affect SLE patients. Objectives: To analyse the obstetric outcome of SLE patients, according to specific therapy received during pregnancy. Methods: A monocentric, retrospective study of 98 SLE patients with a total of 134 pregnancies followed prospectively by multidisciplinary team(1987–2015). Adverse Pregnancy Outcomes(APOs) were defined as one of the followings:premature miscarriage(<10 th week), intrauterine fetal death(>10 th week), perinatal death(<30 th day of life), severe preterm birth(<34 th week) and preterm birth(between 34th-36th weeks). We also evaluated the frequency of other pregnancy complications such as preterm premature rupture of membranes(pPROM) and pre-eclampsia(PE). Results: Among the 134 pregnancies(including 3 twin pregnancies), flares occurred in 10 (7.5%) and APOs in 39 (29.1%) cases (table 1). pPROM complicated 9 pregnancies, all resulted in preterm deliveries, including 3 severe preterm birth; PE complicated 6 pregnancies resulting in 2 preterm birth, 1 intrauterine fetal death, 1 perinatal death and 2 term birth. The rates of APOs, pPROM and PE were compared according to receiving or not a specific therapy: hydroxychloroquine(HCQ), low dose aspirin(LDA), immunosuppressant(IS) during the overall pregnancy and corticosteroids>35 mg/week(CS) during the 1 st, the 2nd and the 3rd trimester. No statistical significant association was found between a specific therapy and the rate of PE. HCQ and LDA did not significantly affected the rate of APOs or pPROM while pregnancies exposed to IS showed a higher frequency of APOs(47% vs 20%, p0.003 ), in particular premature miscarriages(16% vs 2%, p0.007 ). Pregnancies exposed to CS had higher frequency of APOs(1 st trimester 44% vs 28%, p0.015 ; 2nd trimester 36% vs 13% p0.004 ; 3rd trimester 34% vs 14%, p0.019 ). Considering only the 120 pregnancies resulted in live birth, those exposed to CS had higher frequency of preterm birth(1 st trimester p0.006; 2nd trimester p0.023 ; 3rd trimester p0.011 ) (table 2). In particular, pregnancies exposed to CS in the 1 st trimester had higher frequency of preterm birth on 34th-36th w( p0.017 ), while pregnancies exposed in the 3rd trimester had a higher frequency of preterm birth before 34th w( p0.038 ). Furthermore, a higher frequency of pPROM was observed in those exposed to CS(1 st trimester p0.001 ; 2nd trimester p0.003 ; 3rd trimester p0.001 ). Conclusions: Use of IS seems to be associated with premature miscarriages; this could reflect their use in patients with a more severe disease phenotype. The exposure to CS in doses greater than 35 mg/w in the 1 st trimester seems to be associated with preterm birth at 34th-36th w, while in the 3rd trimester with severe preterm birth(<34 th w), that could be related to the strong association observed between CS use and pPROM. Disclosure of Interest: None declared